Wide-angle and polarization-insensitive perfect metamaterial absorber - Kumar R.; Kumar H.; Ramani U.; Kumar S.; Singh B.K.; Singh P.P.; Pandey P.C. (My University, 2025)
We propose a cross-shaped resonator design of a metamaterial (MTM) absorber that shows a 98% average absorbance in the range of 400–1100 nm. This design consists of three layers: a tungsten-based cross-shaped on the top, silicon dioxide (SiO2) in the middle layer, and a tungsten layer at the bottom. The finite integration technique (FIT) method is used to simulate the metamaterial absorber's performance. We have observed the absorber's performance on the different thicknesses of a dielectric layer. We have presented the absorption spectrum for transverse electric (TE) and transverse magnetic (TM) modes for different polarization angles (0◦–90◦) and incident angles (0◦–60◦). Additionally, we have investigated the short-circuit current density for different dielectric layer thicknesses and different incidence angles. This is theoretically analogous to parametric studies. The universal AM 1.5 solar spectrum properties have been used to investigate the feasibility of the proposed MTM absorber as a solar cell. The proposed MTM has many potential uses, including for solar cells. © World Scientific Publishing Company.